2022
DOI: 10.3389/fimmu.2022.925256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Small Peptide Supplementation on Growth Performance, Intestinal Barrier of Laying Hens During the Brooding and Growing Periods

Abstract: The growing period is a critical period for growth and development in laying hens. During this period, chicks grow rapidly, but are accompanied by unstable digestive function, incomplete organ development, and high mortality. Small peptide, a feed additive, which has been proved to promote intestinal development and immunity in poultry. In order to elucidate the effects of small peptides on growth performance, immunity, antioxidant capacity, and intestinal health of growing laying hens, a total of 900 Tianfu g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…As for the economic efficiency, it improved when peptides and vitamin E treatments were added. These results agree with, Zhao et al, [34] who found that by boosting growth rate and illness resistance, the economic value of growing hens was boosted by adding 0, 1.5, 3.0, 4.5, and 6.0 (g/kg) tiny peptides to their diet. As well, the authors indicating that best performance were recorded among the hens fed 4.5 (g/kg) level of small peptide.…”
Section: Growth Performance Parameterssupporting
confidence: 92%
“…As for the economic efficiency, it improved when peptides and vitamin E treatments were added. These results agree with, Zhao et al, [34] who found that by boosting growth rate and illness resistance, the economic value of growing hens was boosted by adding 0, 1.5, 3.0, 4.5, and 6.0 (g/kg) tiny peptides to their diet. As well, the authors indicating that best performance were recorded among the hens fed 4.5 (g/kg) level of small peptide.…”
Section: Growth Performance Parameterssupporting
confidence: 92%
“…Furthermore, some studies have shown that probiotics or their cellular components can improve immune function in animals ( Chen et al, 2022 ). For example, Zhao et al (2022) revealed that dietary supplementation with the small peptides can reduce the proinflammatory factors including IL-6, IL-8 and IL-12 expression, thereby protecting the body from inflammatory damage. Also, Wang et al (2021) showed that dietary addition of Clostridium butyricum and butyric acid glycerides decreased IL-6 content in jejunum of yellow-feathered breeder hens, while those of IL-4, IL-6, IL-1β and IgY were decreased by sodium butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in fold height was observed with the LF diet, which was partially alleviated by the addition of SBP. The increasing addition level of SBP also cubically increased the thickness of the intestinal muscularis; this was a rare occurrence among multiple indicators where SBP demonstrated favourable outcomes even at a 6 % addition level, presumably because SBP is short peptides, which can be directly absorbed and utilised by the intestine and promote intestinal development (43) .…”
Section: Discussionmentioning
confidence: 99%